The Influence of Corporate Governance, Corporate Risk, and Profitability on Tax Avoidance (Empirical Study of Companies Listed in the CGPI Index 2018-2020) - Fetri Setyo Liyundira; Ananda Ajeng Nur Fidiyyah; Deni Juliasari (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2023)
This study seeks to determine and analyze the effect of corporate governance, corporate risk, and profitability on tax avoidance (empirical study of companies listed in the CGPI index 2018-2020). The research method uses descriptive quantitative. The data used is secondary data using the financial statements of listed companies that are the research sample. The population in this study were 15 companies listed in the CGPI index in SWA magazine. The sampling technique used purposive sampling technique so that the sample obtained was 13 companies that met the criteria during 2018-2020. The results of the analysis in the study indicate that good corporate governance and profitability have no effect on tax avoidance. This shows that the higher good corporate governance and profitability will not affect the increase in tax avoidance. Corporate risk has a significant negative effect on tax avoidance. This shows that the higher the corporate risk will lead to increased tax avoidance.